2014 IEEE 6th International Conference on Adaptive Science &Amp; Technology (ICAST) 2014
DOI: 10.1109/icastech.2014.7068099
|View full text |Cite
|
Sign up to set email alerts
|

GA-PID controller for position control of inverted pendulum

Abstract: Stability is very necessary in control system and it becomes more difficult to achieve for a nonlinear system which inverted pendulum is an example. Most of the controllers available suffer from problems such as difficult in tuning process, sluggishness in response time, quick and global convergence etc. This paper considered Proportional-Integra-Derivative optimized with Genetic Algorithm (GA-PID) Controller on Inverted pendulum for the control of the angle position. Conventional PID controller was used to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…In [1] double PID and LQR controllers are designed for inverted pendulum where author used limit cycle criteria based on friction to evaluate control strategies. In [2] an optimal PID controller is designed based on ITAE as performance criteria and genetic algorithm is used to optimize parameters of PID controller. In [3] an optimal LQR controller is designed for inverted pendulum while the weight matrices were selected using PSO optimization method.…”
Section: Introductionmentioning
confidence: 99%
“…In [1] double PID and LQR controllers are designed for inverted pendulum where author used limit cycle criteria based on friction to evaluate control strategies. In [2] an optimal PID controller is designed based on ITAE as performance criteria and genetic algorithm is used to optimize parameters of PID controller. In [3] an optimal LQR controller is designed for inverted pendulum while the weight matrices were selected using PSO optimization method.…”
Section: Introductionmentioning
confidence: 99%
“…The control signal in PID is sum of P-term (which is proportional to the error), the I-term (which is proportional to the integral of the error) and the D-term (which is proportional to derivative of the error). The general representation of PID controller is given in equation 26 [14,31].…”
Section: Pid Control Of Ipipmentioning
confidence: 99%
“…Past literature showed that researchers have shown keen interest in the control of IP system using PID control. Yusuf and Magaji [14] considered PID controller optimized with GA for control of inverted pendulum angle. The PID gains were tuned manually for obtaining an optimum response.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many optimization methods such as genetic algorithm, the bees algorithm, PSO, etc. are used to determine optimum LQR parameters [13][14][15][16][17][18].…”
Section: Fig 1 Inverted Pendulum Modelmentioning
confidence: 99%
“…Fuzzy logic and artificial neural network controllers have been used to obtain more stable control in systems where disturbing input is present [9][10][11][12]. In order to achieve better results from classical PID and LQR type controllers, many studies that used some optimization methods such as bees algorithm [13,14], genetic algorithm [15][16][17] and particle swarm optimization [17,18] have been carried out so that the control parameters can be adjusted appropriately. In this study, optimization of the Linear Quadratic Regulator (LQR) parameters by using Particle Swarm Optimization (PSO) method for balance and position control of the inverse pendulum system is discussed.…”
Section: Introductionmentioning
confidence: 99%